FACTORS AFFECTING THE WORK MOTIVATION OF PLANTATION OVERSEERS AT FAP AGRI LIMITED LIABILITY COMPANY - Sunny, Khalid; Jumiati, Elly; Wahyuni, Etty (Universitas Djuanda, 2024)
This article shows identification about the intrinsic and extrinsic factors that influence the work motivation of supervisors (plant foremen and plant clerks) at PT. FAP AGRI, North Kalimantan. The decline in supervisor motivation at the company has caused issues such as unkempt and undisciplined appearances, as well as an increased resignation rate. This study aims to provide a basis for consideration for the company in making policies to improve the performance of supervisors at PT. FAP AGRI. Data was collected using a census method on 109 supervisors who are training center (TC) graduates and still employed at PT. FAP AGRI. Data collection was conducted using a Likert scale questionnaire and analyzed using Structural Equation Modelling – Partial Least Square (SEM–PLS). The results of the study indicate that the intrinsic factors significantly influencing work motivation include self-perception, self-esteem, personal expectations, and personal needs. The extrinsic factors that influence include the type and nature of the work, work groups, work environment, and salary. The analysis shows that extrinsic factors have a greater influence compared to intrinsic factors on supervisor work motivation. This study provides recommendations for PT. FAP AGRI to focus on enhancing extrinsic factors to improve the work motivation and performance of supervisors